In Search of Our Daughters’ Gardens: Hip Hop as Womanist Prose - Lomax, Tamura A. (Bulletin for the study of religion, 2011)
This essay argues that Alice Walker’s seminal essay, "In Search of Our Mothers’ Gardens," offers a bridge between hip hop and womanist thought that is insightful for theorizing the "daughter’s" (Generation Y) experiences. Moreover, Walkers' essay anticipates hip hop culture, particularly the artistic expressions of female MCs (a.k.a. the "daughters"). One such daughter is current hip hop sensation, Nicki Minaj.